Fungsi Idarah dan Akuntabilitas Pelaporan Keuangan Masjid - M. Nur Abdullah Birton; Juita Tanjung; Maryati; Rendi Emalia (Jurnal Akademi Akuntansi, 2024)
Purpose: This study seeks to achieve three main objectives: (1) discern the actuality of mosque financial reporting; (2) assess stakeholder expectations concerning mosque activities; and (3) evaluate the variance in expectations among stakeholders regarding the reality of mosque financial reporting accountability. Methodology/Approach: The research employs a survey-based approach, utilizing a questionnaire for data collection. The population encompasses congregants, administrators, and supervisors located in the Pasar Rebo District of East Jakarta, including individuals associated with the Indonesian Mosque Council. Questionnaires were disseminated through both online channels using a Google form and through face-to-face interactions. Data were meticulously processed using SPSS 19, employing descriptive and inferential methods such as Analysis of Variance. Findings: The study reveals that all mosques possess financial reports primarily intended for dissemination among the congregation, supervisors, administrators, and particularly, administrators themselves. Stakeholders exhibit a preference for the imarah function of mosques, coupled with a desire for more comprehensive mosque functions. Stakeholders anticipate activity reports, specifically in the form of an annually issued, printed document, submitted during management meetings. The ANOVA test indicates no significant disparities between expectations and the accessibility of financial reports. Practical and Theoretical Contributions/Originality: This research augments existing literature by contributing insights from accountability surveys on mosque financial reporting, concentrating on the viewpoint of stakeholders within a specific geographical region. It extends beyond prior case-specific studies of mosques, enriching our comprehension of mosque financial reporting and accountability from a more comprehensive stakeholder standpoint. Research Limitation: This study is limited within the constrained sample size and an uneven distribution of willing participants among mosques and respondents. The absence of assistance in completing the questionnaire via Google Form introduces the potential for misperceptions and interpretations of instrument items.